2021
DOI: 10.1590/1519-6984.213951
|View full text |Cite
|
Sign up to set email alerts
|

Resource use efficiency of cotton in improved vs conventional planting geometry with exogenous application of bio-stimulant and synthetic growth retardant

Abstract: Plant growth regulators and improved planting density are the innovative techniques in the establishment of more productive cotton crop. A field study was planned to assess the role of growth regulators in the resource utilization efficiency of cotton cultivars under different row spacing at Agronomic Research Area, Bahauddin Zakariya University Multan and Usmania Agricultural Farm, Shujaabad during Kharif 2012. The study was comprised of cotton cultivars viz. CIM-573 and CIM-598, cultivated under conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Thereby, agronomical practices that enhance the water productivity and stabilize cotton yield need to be implemented as a resilience factor under risk’s climate change. Bed planting (conventional row spacing) of cotton has shown ameliorative plant growth, nutrient uptake, and efficient use of available water resources (Hussain et al 2021 ). Thus, bed planting without mulching could be better opt for cotton sowing, water productivity, and cotton yield.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, agronomical practices that enhance the water productivity and stabilize cotton yield need to be implemented as a resilience factor under risk’s climate change. Bed planting (conventional row spacing) of cotton has shown ameliorative plant growth, nutrient uptake, and efficient use of available water resources (Hussain et al 2021 ). Thus, bed planting without mulching could be better opt for cotton sowing, water productivity, and cotton yield.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the cumulative water fluxes were reported more in flood irrigation over mulched drip irrigation (Jin et al 2018). Besides, the bed planting (conventional row spacing) of cotton has shown ameliorative plant growth, nutrients uptake, and efficient use of available water resources (Hussain et al 2021). Therefore, the estimated results strengthen all other advantages of bed planting, i.e., water-saving, uniform distribution, good crop.…”
Section: Groundwater Rechargementioning
confidence: 91%
“…In this regard, other researchers reported that number of squares/plant was increased by application of 1 ml MC/L (Abdel-Aal et al, 2011) and kinetin at 20 ppm (Kassem et al, 2009). Moreover, number of bolls/plant was increased by the application of NAA (Parveen et al, 2017) and MC (Priyanka andDalvi., 2019 andHussain et al, 2021). On the other hand, many investigators found that abscission percentage could be decreased by foliar application of NAA at rate of 30 ppm (Sabale et al, 2017 andGeethanjali et al, 2018).…”
Section: -Flowering and Abscissionmentioning
confidence: 99%
“…The superiority of boll weight may be due to the increase in the photosynthetic production and photoassimilate translocation from leaves to fruits (Zhao and Oosterhuis, 2000). Boll weight and seed index could be increased by application of 30 ppm NAA (Kataria and Khanpara, 2011), and 42 g MC /ha (Hussain et al, 2021) compared to unsprayed cotton plants.…”
Section: -Yield and Seed Qualitymentioning
confidence: 99%